1993
DOI: 10.1111/j.1471-4159.1993.tb03549.x
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR Relaxation Does Not Affect the Quantitation of Changes in Phosphocreatine, Inorganic Phosphate, and ATP Measured In Vivo During Complete Ischemia in Swine Brain

Abstract: Ischemia-induced changes in 31P NMR relaxation were examined in 16 piglets. NMR spectra were acquired under control conditions and during complete cerebral ischemia induced via cardiac arrest. Changes in T1 were assessed directly in six animals during control conditions and after 30-45 min of complete ischemia when changes in brain Pi levels had reached a plateau. The T1 for Pi did not change, i.e., 2.3 +/- 0.5 s during control conditions versus 2.4 +/- 1.0 s during ischemia. To evaluate phosphocreatine and AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…This implies that the T, corresponding to these peaks did not change, and therefore changes in the intensity of peaks in spectra collected using a 1-s interpulse delay should accurately reflect changes in concentration . In analogous past experiments we found that the T, of P;, PCr, and NTP did not change during ischemia (Corbett and Laptook, 1993) .…”
Section: Fig 1 In Vivo 3 'P Nmr Spectra Fora New-supporting
confidence: 79%
See 3 more Smart Citations
“…This implies that the T, corresponding to these peaks did not change, and therefore changes in the intensity of peaks in spectra collected using a 1-s interpulse delay should accurately reflect changes in concentration . In analogous past experiments we found that the T, of P;, PCr, and NTP did not change during ischemia (Corbett and Laptook, 1993) .…”
Section: Fig 1 In Vivo 3 'P Nmr Spectra Fora New-supporting
confidence: 79%
“…The [glucose]r,, ;,,, , ;, in individual animals after injecting insulin or infusing glucose ranged from 1 to 64 mM for newborns and from 2 to 44 mM in 1-month-olds . The [glucose],,, ;, was altered so that glucose-dependent changes in AGR could be studied (see Corbett et al ., 1991Corbett et al ., , 1993 . For the 12 animals kept normocarbic, complete ischemia was induced via the intravenous injection of KCI, and changes in levels of cerebral metabolites were recorded with continuous NMR scanning for 30 min.…”
Section: Surgical Preparation and Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectra were acquired under conditions that did not allow complete relaxation of all 31P and 1912 nuclei [pulse widths of 25 jis for 31P (45°)and 70 jis for '9F (45°)]; however, calculation of [Ca2~I, was assumed to remain unaffected as the spin-lattice relaxation time constant (T 1) values of the free and bound forms of 1 ,2-bis (2-amino-S-phenoxy ) ethane-N,N,N',N'-tetraacetic acid (BAPTA) are similar in tissue (Kirschenlohr et al, 1988). The T1 values for all 31P and 1912 nuclei were assumed to be constant during ischemia [demonstrated for 31P NMR T, values for in vivo brain (Corbett and Laptook, 1993)], allowing comparison of changes in the relative intensity of resonances. Hardware requirements for the pulse sequence included a direct synthesis radiofrequency transmitter and a broadband (or switchable) probe (16 mm id.)…”
Section: Nmr Spectroscopymentioning
confidence: 99%